Cyclic Dipeptide Shuttles as a Novel Skin Penetration Enhancement Approach: Preliminary Evaluation with Diclofenac - Mohammed, Y.; Teixido, M.; Namjoshi, S.; Giralt, E.; Benson, Heather (Public Library of Science, 2016)
This study demonstrates the effectiveness of a peptide shuttle in delivering diclofenac into and through human epidermis. Diclofenac was conjugated to a novel phenylalanyl-N-methyl-naphthalenylalanine-derived diketopiperazine (DKP) shuttle and to TAT (a classical cell penetrating peptide), and topically applied to human epidermis in vitro. DKP and TAT effectively permeated into and through human epidermis. When conjugated to diclofenac, both DKP and TAT enhanced delivery into and through human epidermis, though DKP was significantly more effective. Penetration of diclofenac through human epidermis (to receptor) was increased by conjugation to the peptide shuttle and cell penetrating peptide with enhancement of 6x by DKP-diclofenac and 3x by TAT-diclofenac. In addition, the amount of diclofenac retained within the epidermis was significantly increased by peptide conjugation. COX-2 inhibition activity of diclofenac was retained when conjugated to DKP. Our study suggests that the peptide shuttle approach may offer a new strategy for targeted delivery of small therapeutic and diagnostic molecules to the skin.